Complement Factor H Promotes the Growth of Lung Adenocarcinoma Cells through the JAK2/STAT3 Signaling Pathway - Wang, Kaili; Wang, Xitan; Li, Jiang; Wang, Yangyang; Gao, Peng (Current Cancer Drug Targets, 2025)
BackgroundOver 50% of lung adenocarcinoma patients have high levels of complement factor H (CFH) expression. Previous studies have reported that CFH inhibits the migration of endothelial cells. In this study, we investigated the mechanism by which CFH affects lung adenocarcinoma development via phosphorylation of STAT3.MethodsAdenovirus expressing mice Cfh gene was used to infect C57 mice for two weeks, and then Lewis Lung Carcinoma (LLC) was injected to develop a subcutaneous tumor. The effect of CFH on human A549 cells was also detected. Moreover, we collected CFH over-expressed conditional medium from HepG-2 cells infected with adenovirus expressing human CFH gene. A549 cells were incubated with the conditional medium, and the effect of the CFH-conditional medium on cell proliferation and migration was detected.ResultsIt was found that CFH promoted lung adenocarcinoma growth in vivo, and CFH-conditional medium treatment significantly increased the viability and migration area of A549 cells. CFH-conditional medium increased the phosphorylation of JAK2 and STAT3 in A549 cells. While using STATTIC to block STAT3 phosphorylation, CFH-conditional medium treatment did not affect A549 cell viability or migration compared to the control group.ConclusionThese data suggested that CFH promoted the proliferation and migration of A549 cells by increasing the phosphorylation level of the JAK2/STAT3 signaling pathway. Furthermore, CFH has the potential to be a target for antitumor therapy.
Keywords: proliferation